Peyronie's Disease: A Historical Perspective. (September 2014) - Carriere, Stephen P.; Pytell, Jarratt D.; Saltzman, Amanda F.; Fuselier, Harold A.
Peyronie's disease (PD), more commonly known as penile curvature, is caused by plaque formation in the connective tissue of the penis. PD affects 0.3% to 8.9% of men, most commonly between ages 40 and 60 years and can cause significant psychological distress, regardless of severity. There is a rich history behind the initial reports of PD, initial beliefs about pathogenesis, and initial treatment. This article aims to discuss the history of PD as well as the evolution of causes and treatments throughout time up to present-day theories of pathogenesis and treatment.